Estimating the cost of school sealant programs with minimal data - Griffin, Susan O. (J Public Health Dent, 2017)
OBJECTIVE: Develop methodology to estimate the annual cost of resources used by school sealant programs (SSPs) and demonstrate its use. METHODS: We used existing literature and expert opinion to identify SSP cost components and the most appropriate units for their measurement (e.g., per operator) and collection frequency (e.g., per day). For equipment and reusable instruments, costs were sufficiently homogenous across SSPs that we could provide default per unit cost estimates (2016 US$) that SSPs can use in lieu of collecting their own data. We also provide default costs for supply items such that SSPs can estimate total supply costs with program-specific information on sealant material used, as well as number of: sealant stations, operators, service delivery days, children screened/sealed, and number of teeth sealed. For the remaining three categories (labor, mileage, and administrative), costs varied substantially by SSP and required us to develop and pilot collection logs for program-specific data. RESULTS: The annual cost per sealant station ranged from $584 to $797 depending on program characteristics. For a hypothetical SSP that staffed each of two stations with two operators (hygienist and assistant) compensated at the national rate, hourly labor costs would equal $77.97. Assuming this SSP used disposable instruments, light-cured sealants and delivered sealants (3 per child) to 60 percent of the 3,390 children screened over 100 service days, infection control/supply costs per child would equal $5.30. CONCLUSION: This methodology allows SSPs to estimate costs with minimal data collection and time.